Dementia in Parkinson's disease: Is male gender a risk factor?. (May 2016) - Cereda, Emanuele; Cilia, Roberto; Klersy, Catherine; Siri, Chiara; Pozzi, Beatrice; Reali, Elisa; Colombo, Aurora; Zecchinelli, Anna Lena; Mariani, Claudio Bruno; Tesei, Silvana; Canesi, Margherita; Sacilotto, Giorgio; et al.
Abstract: Background: The rates of cognitive decline in patients with Parkinson's disease (PD) are higher than in the general population. Age and disease duration have been associated with increasing rates of dementia in PD. However, the role of other factors including gender has been poorly investigated. We investigated the relationship between dementia and gender along with other established risk factors, such as age and disease duration. Methods: We conducted a cross-sectional retrospective study including all consecutive patients diagnosed with idiopathic PD attending a single out-patient tertiary clinic over an 18-year period (1995–2013). Dementia was diagnosed according to DSM-IV criteria. Results: Prevalence of dementia was 11.5% (95%CI, 10.8–12.3) and 13.5% (95%CI, 12.7–14.5) in the whole population (N = 6599) and in those aged ≥60 years (N = 5373), respectively. Age and disease duration were independently associated with dementia, and the latter was associated with dementia up to 84 years of age. Male gender was an independent risk factor. In addition, while the rate of dementia increased in males over all age strata, we found that in females prevalence began to increase steadily after the age of 65 years, reaching male estimates only after 80 years of age. Higher rates in male gender were observed between 60 and 80 years of age. Conclusion: Age and PD duration are confirmed risk factors for dementia. However, disease duration appeared to be a less important factor in cognitive decline in patients aged ≥85 years. As opposed to gender-specific estimates in the general population, male gender is likely associated with higher rates of dementia in PD patients. Highlights: Age and disease duration have been associated with higher rates of dementia in PD. The role of other factors including gender has been poorly investigated. Age and PD duration are confirmed risk factors for dementia. However, in patients aged ≥85 years PD duration is likely a less important factor. Male gender is independently associated with higher rates of dementia in PD.